2009
DOI: 10.1177/0146167209335166
|View full text |Cite
|
Sign up to set email alerts
|

From Willingness to Intention: Experience Moderates the Shift From Reactive to Reasoned Behavior

Abstract: Three studies compared the predictive validity of three proximal antecedents to risk behavior: behavioral intention (BI), behavioral expectation (BE), and behavioral willingness (BW). In Study 1, BW was the only significant predictor of change in substance use in early adolescence (age 13), whereas only BI was significant in middle adolescence (age 16). In Study 2, BW was a better predictor of change in smoking among young adolescents than was BE, but BE became predominant by middle adolescence. By late adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
175
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(191 citation statements)
references
References 49 publications
10
175
0
2
Order By: Relevance
“…Previous studies suggest a shift from reactive to planned behaviour with age and experience (Pomery, Gibbons, Reis-Bergan, & Gerrard, 2009), and that the PWM is better at explaining adolescent drinking than young adult drinking (Todd, Kothe, Mullan, & Monds, 2014). Our findings indicate that the social reaction pathway in the PWM may be better able to explain alcohol consumption in younger compared to older adolescents in the UK who have less experience of drinking.…”
Section: Discussionmentioning
confidence: 50%
“…Previous studies suggest a shift from reactive to planned behaviour with age and experience (Pomery, Gibbons, Reis-Bergan, & Gerrard, 2009), and that the PWM is better at explaining adolescent drinking than young adult drinking (Todd, Kothe, Mullan, & Monds, 2014). Our findings indicate that the social reaction pathway in the PWM may be better able to explain alcohol consumption in younger compared to older adolescents in the UK who have less experience of drinking.…”
Section: Discussionmentioning
confidence: 50%
“…Pomery, Gibbons, Reis-Bergan and Gerrard (2009) found that willingness was a stronger predictor of risky behaviour among young adolescents (13 years) with little experience with the behaviour, i.e., substance use, than among middle aged adolescents (aged 16 years) and that intentions became stronger predictors as experience with the behaviour increased. Nevertheless, Gibbons et al (1998b) demonstrated that both willingness and intention are useful predictors of drink driving behaviour, and Rivis et al (2011) showed that applying both the Prototype Willingness Model (PWM) and the TPB provided useful information about the motivational determinants of willingness to drink and drive.…”
Section: Theoretical Considerations and Possible Avenues For Further mentioning
confidence: 92%
“…The results of this study showed that both behavioral willingness and behavioral intention could affect waterpipe smoking and explain 0.55 of the variance, and that behavioral intention was a stronger predictor than behavioral willingness. In most studies of the risky behaviors in adolescents, both the behavioral willingness and behavioral intention constructs had a strong relationship with unhealthy behaviors (10,19,(22)(23)(24). However, the fact that which path could be a stronger predictor of the behavior was different in various studies.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%